Criminological reflections on the regulation and governance of labour exploitation - Davies, Jon (Trends in organized crime, 2020)
The regulation and governance of labour exploitation is a well-researched area across numerous disciplines. Common approaches towards regulating labour exploitation in businesses and supply chains include state interventions to tackle organised crime via the criminal justice system. However, due to strict criminal-legal definitions, these interventions are only possible when targeting severe exploitation. This emphasis means that a large amount of non-criminalised exploitation risks being overlooked. The purpose of this paper is to argue that non-state regulation is an important element in preventing routinised forms of labour exploitation, whereby a criminological perspective would help to understand and better prevent such practices. The paper examines state regulation, self-regulation of businesses, and trade union activity, which together addresses a wider range of labour exploitation. Semi-structured interviews from workers and supply chain stakeholders in the UK agri-food industry are used to inform this discussion. The governance of labour exploitation in relation to business activities hasbroader implications for the disciplinary areas of regulation and (corporate) criminology, whereby the former tends to prioritise restorative and persuasive approaches, whereas the latter focuses on deterrence and coercion. Ultimately, drawing together different strands of regulation into a hybrid approach is useful not only due to socio-political processes, but is arguably the most helpful in addressing routinised exploitation.